2018
DOI: 10.1111/are.13793
|View full text |Cite
|
Sign up to set email alerts
|

Seven transcripts from the chitinase gene family of the mud crabScylla paramamosain: Their expression profiles during development and moulting and under environmental stresses

Abstract: In crustaceans, chitinases (Chts) play crucial roles in physiological functions such as chitinous food digestion, moulting and stress responses. Chitinases have been identified in both prokaryotes and eukaryotes, but the composition and number of Cht family members vary across species, especially in crustaceans. Seven Cht transcripts, all of which contained the conserved enzyme activity motif, were cloned from Scylla paramamosain for the first time, and SpCht1-SpCht6 were clearly classified into groups 1-6, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Further studies have shown that the chitinase expressed in the hepatopancreas and intestines may be mainly related to the degradation of chitin-containing foods and nutrient absorption, whereas the chitinase gene expressed in the epidermis is mainly related to the exoskeleton’s physiological cycle or molting. Additionally, some chitinases expressed in the hepatopancreas, hemocytes and epidermis also participate in immune response mechanisms [ 44 , 49 ].…”
Section: Chitin Degradation Pathways and Gene Familiesmentioning
confidence: 99%
“…Further studies have shown that the chitinase expressed in the hepatopancreas and intestines may be mainly related to the degradation of chitin-containing foods and nutrient absorption, whereas the chitinase gene expressed in the epidermis is mainly related to the exoskeleton’s physiological cycle or molting. Additionally, some chitinases expressed in the hepatopancreas, hemocytes and epidermis also participate in immune response mechanisms [ 44 , 49 ].…”
Section: Chitin Degradation Pathways and Gene Familiesmentioning
confidence: 99%
“…Similar to other crustaceans, growth of S. paramamosain is a stepwise process comprising periodic shedding, subsequent reconstruction of a rigid external exoskeleton and cuticle, and muscle growth to ll the new body during a molting cycle [3,38]. Some functional genes involved in the molting cycle of crabs were identi ed as associated with a series of biological processes in previous studies, for example, in cuticle reconstruction, cytoskeletal structure remodeling, protein synthesis, hormone regulation, immune response, and metabolism [4,13,15,17]. Among these processes, cuticle reconstruction and cytoskeletal structure remodeling have been considered to be essential for all four phases of the molting cycle [33].…”
Section: Expression Patterns Of Degs Associated With Cuticle and Cytomentioning
confidence: 99%
“…Scylla paramamosain (Crustacea: Decapoda: Portunidae), commonly known as the mud crab, is widely distributed along the temperate, subtropical, and tropical areas of the Paci c Ocean and Indian Ocean, and this species is cultivated in many countries. S. paramamosain undergoes molting up to 18 times during its life cycle, including during larval development, during growth-related molting, and in adult reproductive molting [13]. The economic signi cance of this species makes the mud crab a valuable system for exploring the genes involved in the molting cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent studies have explored molting-related genes and their effects on protein synthesis 10 , chitin metabolism 11 , and muscle hydration control 12 during the molting cycle. In addition, great progress has been made in elucidating molting in the last decade by focusing on the effects of environmental factors, the immune system, and endocrine regulation molting, and by conducting gene expression analysis 13 28 . However, the molecular events and mechanisms associated with the dynamic process of molting remain poorly understood in crustaceans, especially in crabs.…”
Section: Introductionmentioning
confidence: 99%